A 19F-MRI probe for the detection of Fe(ii) ions in an aqueous system. Issue 30 (17th June 2020) - Kakiuchi, Ryo; Hirayama, Tasuku; Yanagisawa, Daijiro; Tooyama, Ikuo; Nagasawa, Hideko
Abstract : An activity-based 19 F-MRI probe that showed a chemical shift change in response to Fe(ii ) was developed. Abstract : Iron deposits are often observed in the brains of patients with neurodegenerative diseases, including Alzheimer's and Parkinson's diseases. This study outlines the development of F-Nox-1 as the first example of a 19 F-MRI probe that can selectively detect Fe(ii ) in aqueous solutions. The use of tetrafluoro- p -phenylenediamine (TFPDA) as a 19 F signal emitter with an Fe(ii )-selective chemical switch, based on our previously reported N -oxide chemistry, yielded a readout of a symmetry-dependent 19 F signal change in response to Fe(ii ). The addition of Fe(ii ) ions to F-Nox-1 triggered a 19 F signal change, both in the chemical shift and signal intensity, and the response was highly selective to Fe(ii ) over other biologically relevant metal ions. The probe could also detect Fe(ii ) in serum containing various biological contaminants by 19 F magnetic resonance imaging ( 19 F-MRI). Imaging of soluble Fe(ii ) species, which is the major component of water-soluble iron species, by 19 F-MRI will potentially enable the direct monitoring of the elevation of Fe(ii ) levels prior to the formation of iron deposits, which is a potential risk factor for neurodegenerative diseases.